AN ERROR ANALYSIS OF USING SIMPLE PRESENT TENSE IN DESCRIPTIVE TEXT AT THE GRADE VIII MTs MUHAMMADIYAH 22 PADANGSIDIMPUAN - Wahyuni, Bunga Sri (jurnalalfa, 2023)
An Error Analysis of Using Simple Present Tense in Descriptive Text at The Grade VIII MTs Muhammadiyah 22 Padangsidimpuan (2018). The purpose of this study is to analyze of student’s errors on the use of present tense in Descritpive text based on the problem that students felt confused about using present tense in their writing especially Descriptive text. The method of study is qualitative descriptive. The subject of study writer chose VIII-A class (2021/2022) in MTs Muhammadiyah 22 Padangsidimpuan. Data collection techniques by instructing students to write descriptive text with a given theme. The data were analyzed using descriptive analysis methods and classified the types of errors and the writer gave check in the observation checklist. The result show that the reseacher found four types of errors: omission, addition, misformation, misodering. Then, the writer found the highest error made by students is misformation with 37% percentages. This problem influenced by student felt confused to understand simple present tense because they didn't understand the use and placement of to be on the chosen subject. Therefore, students claimed if they seldom to practice writing paragraph.